DIKSI METAFORIS RUANG PARIWISATA ALAM DALAM KUMPULAN PUISI DAN CERITA PENDEK PULANGLAH KE RUMAH - Muhammad Amirul Halim; Gatot Sarmidi ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2025)
One of the interesting literary studies is the study of literary texts in terms of their aesthetic media. The interdisciplinary relationship between literature and language is studied in stylistics. Diction and metaphor are widely discussed in poetry studies. There are not many studies of diction and metaphor that are specifically oriented to the study of poetry that is classified as nature tourism literature. The research method used is literary research that is carried out qualitatively and applies hermeneutics as a method in interpreting texts descriptively. The research data in the form of selected poetry texts based on metaphorical diction, data sources in the form of a textbook of a collection of poetry and short stories entitled Pulanglah ke Rumah, data collection based on observation and interview techniques, data analysis using interactional data analysis techniques and interpreted hermeneutically. Based on the results of the study, it can be concluded that the diction used in the poem Pulanglah ke Rumah contains a lot of metaphorical diction. This proves that the author in creating a work considers the aspect of beauty presented in a fiction based on the surrounding conditions. In addition, this study illustrates the author's competence in producing tourism literature.